The relationship between maternal knowledge and stunting incidence in children under five in Kendari City - Herman, Herman; Saleh, Firmansyah; La Ode , Diki Insani (Indonesian Nursing Journal, 2025)
Background: Stunting, a form of chronic malnutrition, remains a significant public health issue in Indonesia. Maternal knowledge about nutrition and childcare is a critical factor in preventing stunting. However, the specific relationship between maternal knowledge and stunting incidence in Kendari City is underexplored. Purpose: This study aims to analyze the relationship between maternal knowledge and stunting incidence in children aged 6-59 months in Kendari City. Methods: A cross-sectional study was conducted with 200 mothers of children under five. Data were collected using structured interviews to assess maternal knowledge and anthropometric measurements to determine stunting status. Statistical analysis included chi-square tests and logistic regression to examine associations and identify significant predictors of stunting. Results: The incidence of stunting among respondents' children was 40%. Low maternal knowledge was significantly associated with stunting (p < 0.05). Logistic regression identified low maternal knowledge (AOR = 2.89, 95% CI: 1.53–5.45) and low household income (AOR = 2.35, 95% CI: 1.22–4.51) as dominant risk factors. Conclusion: Low maternal knowledge is a significant contributor to stunting in Kendari City. Targeted nutrition education and socio-economic interventions are essential to address this issue.